Microemboli After Successful Thrombectomy Do Not Affect Outcome But Predict New Embolic Events - Mariana Fernandes Diz Lopes (2020)
Background and Purpose: To determine if microemboli after endovascular thrombectomy correlate with unfavorable outcomes despite successful recanalization. Methods: This is a prospective multicenter study of consecutive patients with ischemic stroke and occlusion of anterior circulation vessels (terminal internal carotid or M1/M2 segments of middle cerebral artery) after successful thrombectomy (modified Treatment In Cerebral Ischemia grades 2b-3). Microembolic signals (MES) were assessed by 30-minutes of transcranial Doppler (TCD) monitoring within 72 hours of the last-seen-well time. Major outcomes included modified Rankin scale at 90 days and infarct volume on head CT at 24 hours. We also assessed early outcomes based on NIHSS variation and recurrence of stroke, TIA, or systemic embolism within 90 days. Results: Among 111 patients, MES were detected in 43 (39%), with a median rate of 4 counts/hour (interquartile range 2 - 12). The occurrence of MES was not associated with a significant difference in mRS (ordinal shift analysis, adjusted odds ratio 1.06 (95% CI 0.48 - 2.34), p = 0.85) nor in functional independence (mRS 0 - 2: adjusted odds ratio = 0.52 (95% CI 0.19 - 1.39), p = 0.19). Patients with and without MES had similar infarct volumes (adjusted beta = 11.2 (95% CI - 46.6 - +22.9), p = 0.51) on 24-hour CT. MES did predict new embolic events (adjusted Cox hazard ratio 6.78 (CI 95% 1.63 - 27.8), p=0.01). Conclusions: Microembolic signals detected by TCD following endovascular treatment of anterior circulation occlusions do not predict clinical or radiological outcome. However, such emboli are an independent marker of recurrent embolic events within 90 days.